Aquitanian and Vasconic (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2020)
This work deals with the linguistic situation of Aquitaine and Vasconia in Antiquity. The preserved documentation, of an onomastic nature, proves the existence of a language or linguistic varieties closely related to the Basque language. The specific characteristics of the documentation and the textual and methodological problems are discussed at the same time of its description, analysis and linguistic explanation.
Keywords: Aquitanian; Basque language; Onomastics; Palaeohispanic epigraphy